New evidence for the validity of Coprophanaeus (C.) terrali Arnaud, 2002 (Coleoptera: Scarabaeidae: Scarabaeinae: Phanaeini), a dung beetle from Brazil - Cupello, Mario; Vaz-De-Mello, Fernando Z. (Zootaxa, 2013)
Coprophanaeus terrali, a species based on a single male from Sinop, Brazil, had its validity questioned recently when it was suggested that its tetratuberculate cephalic carina could be just an individual variation of C. dardanus (MacLeay, 1819). In this work, based on three additional males and two females collected near the type locality, we present new evidence supporting the validity of this species, discuss the variation of the male cephalic carina and describe the female morphology for the first time.